Pendampingan UKK Teknik Kendaraan Ringan Otomotif SMK Negeri 1 Kotaanyar Paiton - Djoko Wahyudi; Fathuddin, Muhammad; Eva Kurnia Yulyawan; Lukman Hakim (Jurnal Pengabdian Ahmad Yani, 2024)
The tridharma of higher education is education, research, and community service. One of these obligations is carrying out community service, which is carried out in relation to the concerns of every institution or institution operating in the field of education. The community service carried out at SMK Negeri 1 Kotanyar is a form of implementation of the Tridharma of Higher Education by providing assistance as well as serving as an external examiner in the Skills Competency Test. This Community Service Program focuses on activities carried out on the Automotive Light Vehicle Engineering skills program with material including Tune Up, Chassis, Automotive Electrical, and AC (Air Conditioning) Systems. The results of the skills competency test are given a weight that has been regulated in the assessment rubric, namely 70% for the skills aspect and 30% for the knowledge aspect. Based on the results of the exams carried out by all participants, it can be seen that the recapitulation of the Skills Competency Test results at SMK Negeri 1 Kotaanyar shows that the overall average of students at SMK Negeri 1 Kotaanyar received a final score of "Competent" in the field of light vehicle engineering expertise. automotive.